The Palgrave Handbook of Youth Mobility and Educational Migration - Cairns, David (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This handbook provides an overview of developments in the youth mobility and migration research field, with specific emphasis on movement for education, work and training purposes, encompassing exchanges sponsored by institutions, governments and international agencies, and free movement. The collection features over 30 theoretically and empirically-based discussions of the meaning and key aspects of various forms of mobility as practiced in contemporary societies, and concludes with an exploration of the costs and benefits of moving abroad to individuals and societies at a time when the viability of free circulation is being called into question. The geographical scope of the book covers Europe, Asia, Australia and the Americas, and takes into account socio-economic and regional inequalities, as well as recent developments such as the refugee crisis, Brexit and the Covid-19 pandemic. The book integrates the fields of youth mobility and migration studies, creating opportunities for the establishment of a new paradigm for understanding the spatial circulation of youth and young adults in the twenty-first century.
1. Introduction: The Intermittency Of Youth Migration -- Part I 2. Introducing Youth Mobility And Migration -- 3. Mobility Becoming Migration: Understanding Youth Spatiality In The Twenty-First Century -- 4. Migration Decision-Making, Mobility Capital And Reflexive Learning -- 5. Inherited Dreams Of 'The West': Eastern European Students' Paths To Denmark -- 6. Unpacking The Mobility Capacities And Imperatives Of The 'Global Generation' -- 7. Why Student Mobility Does Not Automatically Lead To Better Understanding: Reflections On The Concept Of Intercultural Learning -- Part II 8. Free Movement In Education -- 9. Youth Educational Mobility: The Start Of Intellectual Migration -- 10. Understanding Educational Migration From Greece To The UK In Times Of Crisis -- 11. Transnational Mobility, Education And Social Positioning Between Brazil And Germany -- 12. Refugees' Access To Higher Education In Italy: An Opportunity Lost For The 'Lost Generation -- 13. After Mobility: The Long-Term Impact Of Study Abroad On Professional Teacher Behaviour -- 14. Dispositives Of Internationalization In Brazilian Science: The Unified Postgraduate Examination In Physics -- 15. 'I Had To Move Somewhere:' Leaving Finland To Study In Sweden -- Part III 16. Institutionalized Mobility Inside And Outside Erasmus -- 17. Erasmus At 30: Institutional Mobility At Higher Education In Perspective -- 18. Learning In Transition: Erasmus+ As An Opportunity For Internationalization -- 19. Mobility And Participation: The Intertwined Movement Of Youth And Ideas -- 20. The Super-Mobile Student: Global Educational Trajectories In Erasmus Mundus -- 21. Educational Mobility Of South African Youth: Insights From Erasmus Mundus Action 2 -- 22. Intra-Regional Academic Mobility In Central Asia: The OSCE Academy In Bishkek, Kyrgyzstan -- 23. South-South Student Mobility: International Students From Portuguese-Speaking Africa In Brazil -- 24. Mobile And Immobile Students' Characteristics And Programme Choices -- 25. Identity Challenges And Pedagogical Consequences: International Students In Higher Education Pathway Programmes In Australia -- Part IV 26. Working Towards Mobility -- 27. Beyond Skills: Facets Of Mobility In Romania's Vocational Education And Training -- 28. Using Cross-Border Mobility In Vocational Education And Training In The Greater Region Saarlorlux -- 29. Vocational Learning Abroad: The Case Of German VET Mobility -- 30. Youth As Temporary Workers Abroad: The Experiences Of Australia, Canada And New Zealand -- 31. International Work Placements: Developing Intercultural Skills? -- 32. Abroad Forever? Embedding Spatial Mobility In Academic Work Trajectories In Italy -- 33. Italian Youth And The Experience Of Highly Qualified Migration To The United Kingdom -- Part V 34. Mobility At The Margins -- 35. Mobility Choices In Post-Soviet States: How The EU Attracts Youth In Its Shared Neighbourhood With Russia -- 36. From Forced Migration To Mobility: Dreaming Of Home Within 'Rooted Mobilities' -- 37. 'I Was Not Prepared To Go To Spain': Work Mobility Of Young People At The Margins In Portugal -- 38. Crossing The Line: Current And Future Challenges In Youth Mobility -- 39. Youth Mobility, Mental Health And Risky Behaviours -- 40. Rethinking The Value(S) Of Short-Term Youth Mobility: Neoliberal Ideals And Counterhegemonic Possibilities -- 41. A Wonderful But Uncertain Time: Youth Transitions Of Erasmus Students And Lisbon's Housing Crisis -- 42. Conclusion: Youth Migration In The Age Of Pandemic Immobility.
Keywords: Emigration and immigration; Sociology; Social groups; Industrial sociology; Sports-Sociological aspects; Sports sciences; Human geography; Human Migration; Sociology of Family, Youth and Aging; Sociology of Work; Sport Sociology; Sport Science; Human Geography